2017
DOI: 10.1021/acs.orglett.7b01137
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fused Polycyclic 1,4-Benzodiazepines via Metal-Free Cascade [5 + 2]/[2 + 2] Cycloadditions

Abstract: A metal-catalyst-free, mild, and efficient synthetic protocol for polycyclic 1,4-benzodiazepines via cascade [5 + 2]/[2 + 2] cycloadditions between pyridinium zwitterions and arynes is reported. Mechanistic experiments revealed that pyridinium zwitterions act as 1,5-dipoles in [5 + 2] cycloadditions with arynes for the construction of 1,4-benzodiazepines, which further undergo [2 + 2] cycloaddition resulting in the one-pot formation of one C-N bond and three C-C bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…17 We found that CyPYs display similar chemical reactivity to cyanosulfurylides, but can be electronically tuned by substituent groups on the aromatic ring. 18,19 We were further encouraged by early reports from Taylor implying that cyanopyridiniumylides can be converted to free carboxylic acids by treatment with acid. 20 While pyridinium ylides are commonly employed as building blocks in organic chemistry, the more stabilized CyPYs have received less attention, likely due to their relatively low reactivity.…”
Section: Methodsmentioning
confidence: 99%
“…17 We found that CyPYs display similar chemical reactivity to cyanosulfurylides, but can be electronically tuned by substituent groups on the aromatic ring. 18,19 We were further encouraged by early reports from Taylor implying that cyanopyridiniumylides can be converted to free carboxylic acids by treatment with acid. 20 While pyridinium ylides are commonly employed as building blocks in organic chemistry, the more stabilized CyPYs have received less attention, likely due to their relatively low reactivity.…”
Section: Methodsmentioning
confidence: 99%
“…[100] The main benefits of this new method include novelty, operational simplicity, and good yields (Scheme 23). The synthesis of 2-amine polysubstituted indolizine (124) was reported by Coffinier [101] et al using pyridines (121), halogenides (122) and phosphorylated hydroxyketenimines (123). The ketenimines are easily produced via an isocyanides involving cascade reaction (Nef-Perkow).…”
Section: Pyridinium Salts In Mcrsmentioning
confidence: 99%
“…[120,121] The catalytic multicomponent [ The same group developed later on a one-pot, straight forward domino [5 + 2]/[2 + 2] cycloaddition reactions leading to pentacyclic heterocycles. [122] Pyridinium zwitterions (174) acted as specific 1,5-dipole in metal-free [5 + 2] dipolar cycloadditions reaction with (175). It resulted in the formation of 1,4-benzodiazepines whose further [2 + 2] cycloadditions with other arynes lead to the end product (176) (Scheme 34).…”
Section: Pyridinium 14-zwitterions In Mcrsmentioning
confidence: 99%
“…This cycloaddition enabled the facile construction of eight-membered heterocyclic compounds that were otherwise difficult to access.To demonstrate the synthetic utility of the proposed methodology, a stereoselective version of the [5 + 3] cycloaddition of tert-butyldimethylsilyl (TBS)-protected enol diazoacetate was optimized using [Rh 2 (S-PTAD) 4 ] as the catalyst in toluene at 0 • C. The corresponding cycloadduct A (Scheme 39 cycloadduct A, R 1 = 2-Ph, R 2 = Ph, R 3 = Ts) was obtained in good yield and with 93% ee. As part of their interest in the cycloadditions of pyridinium zwitterions for the preparation of heterocyclic compounds, Yoo and co-authors [116] developed an efficient and metal-catalyst-free synthetic protocol that provided fused 1,4-benzodiazepine derivatives via cascade [5 + 2] As part of their interest in the cycloadditions of pyridinium zwitterions for the preparation of heterocyclic compounds, Yoo and co-authors [116] developed an efficient and metal-catalyst-free synthetic protocol that provided fused 1,4-benzodiazepine derivatives via cascade [5 + 2] As part of their interest in the cycloadditions of pyridinium zwitterions for the preparation of heterocyclic compounds, Yoo and co-authors [116] developed an efficient and metal-catalyst-free synthetic protocol that provided fused 1,4-benzodiazepine derivatives via cascade [5 + 2] A mechanistic rationale for this cascade reaction was proposed by the authors. The pyridinium zwitterion reacted with the benzyne (for related benzyne-promoted, dearomatization of pyridine derivatives see [117,118]) generated in situ from 2-(trimethylsilyl)phenyl trifluoromethanesulfonate and led to the formation of 1,4-benzodiazepine; this first [5 + 2] cycloaddition seemed to be the rate-determining step because it involved the dearomatization of the pyridinium zwitterion.…”
Section: Pyridinium Zwitterionsmentioning
confidence: 99%